Methodological aspects of the application of innovation technologies in the construction industry of Azerbaijan (Economics and region, 2023)
Methodological aspects of the application of innovation technologies in the construction industry of Azerbaijan are studied in the article. It is noted that although the construction industry of the Republic of Azerbaijan developed at a fairly high rate during the years of independence, technologically, especially regarding the application of promising technologies, the expected level has not been achieved, and still the main part of the construction works in the republic is carried out using more traditional materials. Such a situation is especially evident in housing construction. From this point of view, it is justified in the article that the production of green building materials is important and important. Here we are talking about organizing the production of construction materials that serve to eliminate the damage to the environment and the human body. In this regard, the article tried to explain the main features that distinguish green building materials from other traditional building materials. The article also shows that the development of the construction industry is an important and integral part of innovation activity in the country, and innovations in this field play an important role in the development of the country's economy and its individual regions. As a continuation of the research, the article explains the importance of solving methodological approaches for the implementation of innovation policy in construction enterprises and offers suggestions in this direction. Thus, it is noted that in order to implement the innovation policy in construction industry enterprises, an innovation policy should be formulated and the activities of individual production units should be coordinated, a purpose-program group should be created to solve innovation problems, plans and programs of innovation activities should be prepared, innovation activity programs should be financed and material resources should be provided, programs for the creation of new construction products should be reviewed, innovation activities should be provided with qualified personnel, the progress of the process of development and application of new products should be monitored, etc. such methodological approaches should be resolved. At the same time, the article argues that creating equal conditions for competition between subjects during the implementation of innovations in the construction industry will reduce the resource intensity, energy and labor costs of the production of construction products. In general, research was conducted on the problems mentioned in the article in Azerbaijan, results were obtained in this direction and suggestions were made.
Keywords: construction; industry; material; production; innovation; technology; methodology; green building material